Analisis Yuridis Pelarangan Penggunaan Lagu oleh Pencipta Lagu Performer - Mochamad Aidil Adam; Yudho Taruno Muryanto (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to determine the legal protection of performer song creators for the use of created songs that are commercialized without permission by the concert organizer. This research was conducted with juridical-normative research, which is sourced from primary legal materials from laws and regulations, while secondary data is obtained from written legal materials such as scientific journals, books, scientific articles, laws and regulations, and other related literature materials. The results of this study show that legal protection for song creators has been regulated in Law Number 28 of 2014 concerning Copyright. The protection provided by the UUHC to songwriters who are performers has not provided maximum protection. Therefore, it is necessary to regulate the intellectual property rights of performer songwriters and non-performer songwriters.